Sutureless transplantation of in vivo priming human mesenchymal stem cell sheet promotes the therapeutic potential for cardiac repair. (1st January 2023) - Choi, Andrew; Kim, Hyeok; Han, Hyeonseok; Park, Jae-Hyun; Kim, Jin-Ju; Sim, Woo-Sup; Lee, Seong Jin; Ban, Kiwon; Park, Hun-Jun; Kim, Dong Sung
Abstract: The heart, contrary to its small size, vigorously pumps oxygen and nutrients to our entire body indeterminably; and thus, its dysfunction could be devastating. Until now, there ave been several major obstacles to applying a cardiac patch for the treatment for myocardial infarction, including poor integration and low engraftment rates, due to the highly-curved surface of the heart and its dynamic nature. Here, we demonstrate a novel way for a comprehensive cardiac repair achieved by the sutureless transplantation of a highly integrable in vivo priming bone marrow mesenchymal stem cell (BMSC) sheet based on the utilization of a highly aligned thermoresponsive nanofiber membrane. Moreover, we developed a BMSC sheet specialized for vascular regeneration through ' in-vivo priming' using human umbilical vein endothelial cells. A prolonged secretion of multiple angiogenic cytokines, such as vascular endothelial growth factor, angiopoietin-1, insulin-like growth factor-1, which was observed in vitro from the specialized BMSC sheet seemed to lead a significant improvement in the cardiac function, including intrinsic contractibility and remodeling. In this study, we provide strong evidence that in vivo priming of a human BMSC sheet develops the therapeutic potential for cardiac repair.